Characteristics of Local Endograms at the Site of Successful Arrhythmia Suppression During Activation Mapping of Idiopathic Ventricular Arrhythmias Using 3D Navigation - Serhii Yu. Prorok; Yelizaveta O. Lebedieva (Ukrainian Journal of Cardiovascular Surgery, 2024)
A topical issue is the determination of the optimal values of activation time of local endograms (LE) and bipolar signal morphology during ablation in patients with idiopathic ventricular arrhythmias (VA) at the site of successful suppression, and the influence of 3D navigation on these values.The aim. To study earliest activation time (EAT) and LE morphology in the area of successful suppression during ablation of idiopathic VA using 3D navigation.Materials and methods. Analysis of the results of ablation in 57 patients with idiopathic VA was made. The patients were divided into two groups. Group I included 30 (52.6%) patients in whom mapping was performed using 3D navigation (EnSite Velocity Cardiac Mapping System). Group II included 27 (47.4%) patients who were mapped using conventional methods.In group I, extrasystole was found in 20 (66.7%) patients, while ventricular tachycardia was observed in 10 (33.3%) patients. In group II, extrasystole was revealed in 16 (59.3%) patients, and ventricular tachycardia in 11 (40.7%) patients.Group I included 21 (70%) patients with right ventricular localization of arrhythmia and 9 (30%) patients with left ventricular localization. Meanwhile, group II included 17 (63%) patients with a focus in the right ventricle and 10 (33%) patients with that in the left ventricle.The morphology of the LE was evaluated according to criteria such as polarity (positive or negative) and degree of signal fragmentation (monomorphic or fragmented). Polarity was determined by the initial direction of the signal during the first 10 ms, regardless of further changes in the endogram. The signal was considered fragmented if there were three or more polarity changes.Results. In group I, EAT of LE was -38.0±7.0 ms, while in group II it was -38.0±8.5 ms. No difference was found between the studied groups (p=0.834).Among all patients in both groups, the average value of EAT of LE at the site of successful arrhythmia elimination was -37.0±8.5 ms. In 92.9% cases EAT of LE was -30 ms or earlier. Only in four (7.1%) patients it was possible to achieve suppression of the arrhythmia with EAT of LE not earlier than -30 ms, while in all these cases the focus was always localized in the right ventricle. The minimum value of EAT of LE at the site of successful suppression of arrhythmia was -27 ms.The dominant morphology at the site of successful suppression among the patients in both groups, regardless of the type of mapping, was positive polarity of endogram.Conclusions. Regardless of the mapping method, in the site of successful idiopathic VA suppression LE must precede QRS by at least 27 ms.